1993
DOI: 10.1103/physrevlett.70.1187
|View full text |Cite
|
Sign up to set email alerts
|

Coherent states via decoherence

Abstract: The rate at which pure initial states deteriorate into mixtures is computed for a harmonic oscillator interacting with an environment in thermal equilibrium. The decoherence process resulting from this interaction selects a set of states characterized by maximal stability (or minimal loss of predictive power) which can be quantified by the rate of increase in either linear or statistical entropy. In the weak cou- It was shown for various idealized models (invented primarily to study the "reduction of the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
689
1
12

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(732 citation statements)
references
References 21 publications
30
689
1
12
Order By: Relevance
“…For a free electron decohered only by 300K photons, for instance, ∆x∆p ≈ 10 11h . This conclusion is likely to be valid quite generally, also when the initial state is not of the form assumed above, since recent work by Zurek, Habib and Paz [32] has indicated that quite general states tend to approach generalized coherent states (states with a Gaussian Wigner function) when they interact with their environment. This paper has focused entirely on scattering.…”
Section: Coherence Lengthsmentioning
confidence: 90%
“…For a free electron decohered only by 300K photons, for instance, ∆x∆p ≈ 10 11h . This conclusion is likely to be valid quite generally, also when the initial state is not of the form assumed above, since recent work by Zurek, Habib and Paz [32] has indicated that quite general states tend to approach generalized coherent states (states with a Gaussian Wigner function) when they interact with their environment. This paper has focused entirely on scattering.…”
Section: Coherence Lengthsmentioning
confidence: 90%
“…This parameter represents a linear entropy for the conditionalρ matrix [17]. Let us consider the particle scattering in a dense matter and derive an average description of its propagation for a relatively large, macroscopic time of flight.…”
Section: Propagation In Environmentmentioning
confidence: 99%
“…Новая концепция состоит во введении жестких (robust) состояний, которые обра-зуют оптимальный базис для представления статистического оператора с помощью матрицы плотности [1], [15]. Декогерентность возникает как затухание недиагональ-ных элементов.…”
Section: к гокке г рёпкеunclassified